2002
DOI: 10.3201/eid0810.020398
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Sampling for Spores ofBacillus anthracis

Abstract: On November 11, 2001, following the bioterrorism-related anthrax attacks, the U.S. Postal Service collected samples at the Southern Connecticut Processing and Distribution Center; all samples were negative for Bacillus anthracis. After a patient in Connecticut died from inhalational anthrax on November 19, the center was sampled again on November 21 and 25 by using dry and wet swabs. All samples were again negative for B. anthracis. On November 28, guided by information from epidemiologic investigation, we sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 5 publications
0
31
0
3
Order By: Relevance
“…Since the anthrax attacks in 2001, sampling methods using wipe and vacuum collection devices have been developed to meet the needs of a broader range of applications, including building characterization and clearance. Data accumulated from sampling of contaminated facilities in 2001 using HEPA vacuum, dry and premoistened swab, and wipe sampling methods demonstrated that sampling efficiency was dependent on surface sampling techniques and sample collection conditions (42,47).Overall recovery efficiency is sensitive to the applied experimental conditions due to a wide range of potential variables in surface sample collection methodologies, such as differences in extraction solution, adsorptive material, surface substrate, and surrogate biomaterial. The performance of sampling methodologies is typically studied by depositing known quantities of a particular microorganism on a surface, removal of this microorganism using an adsorptive material, and extraction of the microorganism from the adsorptive material (18,22,26,27,48).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the anthrax attacks in 2001, sampling methods using wipe and vacuum collection devices have been developed to meet the needs of a broader range of applications, including building characterization and clearance. Data accumulated from sampling of contaminated facilities in 2001 using HEPA vacuum, dry and premoistened swab, and wipe sampling methods demonstrated that sampling efficiency was dependent on surface sampling techniques and sample collection conditions (42,47).Overall recovery efficiency is sensitive to the applied experimental conditions due to a wide range of potential variables in surface sample collection methodologies, such as differences in extraction solution, adsorptive material, surface substrate, and surrogate biomaterial. The performance of sampling methodologies is typically studied by depositing known quantities of a particular microorganism on a surface, removal of this microorganism using an adsorptive material, and extraction of the microorganism from the adsorptive material (18,22,26,27,48).…”
mentioning
confidence: 99%
“…Since the anthrax attacks in 2001, sampling methods using wipe and vacuum collection devices have been developed to meet the needs of a broader range of applications, including building characterization and clearance. Data accumulated from sampling of contaminated facilities in 2001 using HEPA vacuum, dry and premoistened swab, and wipe sampling methods demonstrated that sampling efficiency was dependent on surface sampling techniques and sample collection conditions (42,47).…”
mentioning
confidence: 99%
“…A physical difference in the spore deposition patterns was observed to result from the two different methods. The spore deposition method developed in this study will help prepare spore coupons via aerosolization fast and reproducibly for bench top decontamination and detection studies.In response to the 2001 Bacillus anthracis spore incidents in the United States, many studies have investigated various technologies to sample media, detect biological agents, and decontaminate materials (3,9,10,(17)(18)(19)21). These laboratory studies typically use small coupons and laboratory inoculants to simulate the materials and biological agents that occur in field events.…”
mentioning
confidence: 99%
“…Restoring a transportation facility requires the analysis of a large number of samples, both environmental samples and biological indicators, during the characterization, remediation verification, and clearance stages (Corrigan 2003;Teshale, et al 2002). Analysis of these samples is currently accomplished by traditional culture based methods which determine spore viability by visual inspection for growth in a culture broth 7 to 14 days after inoculation.…”
Section: Overviewmentioning
confidence: 99%